Pastoralist appropriation of landscape by means of rock art in Ennedi Highlands, Chad - Tilman Lenssen-Erz (OpenEdition, 2012)
Research into the Saharan rock art has from the very first day been linked to the question of how the people of the past managed to live in this environment. It was about the enigma of climatic conditions and cattle herders who obviously once inhabited regions that meanwhile have become uninhabitable desert. The first rock picture discovered by a European researcher was the “Apollon Garamante” showing two masked persons on the side of cattle (Barth 1857: 210). This made the discoverer Heinrich Barth wonder about the possibilities of keeping cattle in this region, the Libyan Messak Settafet, and the necessarily more advantageous former climate (ibid.: 215-218). At this juncture, it is worth noting that there is ubiquity of cattle in Saharan rock art on the one hand, but, on the other hand, that the “green Sahara” never was anything like the deep green meadows of Europe. Accordingly this land never sustained permanent habitation that could settle in a certain place for centuries (except for the oases), even if the economic system would not have necessitated mobility such as in a hunter-gatherer economy. Therefore this paper seeks to elucidate the hypothesis that the appropriation of the land and the advertisement of identities by prehistoric Saharan pastoralists of the Ennedi Highlands were not effectuated by settlements and built structures but through rock art in various expressive forms.